Emotional Intelligence in Institutionalized and Non-Institutionalized Children and Adolescents: A Comparative Study. - Condor-Vela, Samantha (2024)
The objective of the research was to compare the levels of emotional intelligence in a sample of institutionalized and non-institutionalized children and adolescents in Quito, Ecuador. The research adopts a comparative, cross-sectional quantitative approach using the Emotional Quotient Inventory EQi-YV BarOn. Sixty children and adolescents participated (56% female, 44% male) aged 7 to 17 years (M=11 years; SD= 3.18), where 30 of them belong to a foster home and the rest to a private institution in the city of Quito, Ecuador. Significant differences are found, as institutionalized children and adolescents have lower and average levels of emotional intelligence compared to those not under institutional care, the majority of whom have higher levels of emotional intelligence. In conclusion, the emotional lessons learned during childhood and adolescence become critical windows of opportunity to establish essential emotional habits that will be part of our lives.